Sonified Cryptography: Secure Text Encoding with DNA and Non-Speech Audio - Chandrasekaran Saravanakumar; Neelamegam Subhashini (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2025)
The increasing demand for data security in digital communication, particularly in high-risk sectors like defense, has led to the exploration of innovative encryption approaches. This study presents a dual-layer encryption model that enhances information concealment by integrating DNA-based cryptography with audio signal encoding. Initially, plaintext is converted into binary and obfuscated using XOR operations with randomly generated DNA sequences. The resulting DNA nucleotide sequences (A, G, C, T) form the first layer of encryption. In the second layer, these sequences are audified by mapping each nucleotide to a specific frequency, thereby transforming the encrypted data into non-speech audio signals. To evaluate the integrity and uniqueness of the encryption-decryption process, Fast Fourier Transform (FFT)-based cross-correlation is applied, comparing the original and recovered audio signals. The proposed method is implemented in MATLAB and tested on various input strings. Results demonstrate significant improvements in encryption speed and security, with the added benefit of imperceptibility in audio form. The method outperforms existing DNA-based techniques in terms of computational efficiency and resistance to brute-force attacks. This hybrid cryptographic technique offers a promising solution for secure, covert data transmission in sensitive applications.